THE ROLE OF EVIDENTIALITY IN EXPRESSING PERCEPTION IN UZBEK AND ITS ABSENCE IN ENGLISH - Karabaeva Barno Bobir qizi (Western European Studies, 2025)
Evidentiality, the linguistic encoding of information source, constitutes a key dimension in how speakers express perception, certainty, and reliability of statements. In Turkic languages such as Uzbek, evidentiality manifests overtly through morphological markers that convey whether knowledge stems from direct experience, inference, or hearsay. By contrast, English exhibits no dedicated evidentiality markers; instead, it relies on lexical or modal constructions to signal varying degrees of certainty or source of information. This article investigates the role of evidentiality in expressing perception in Uzbek, focusing on how morphological and syntactic devices articulate the speaker’s relationship to the perceived event. Through a comparative lens, we examine how English speakers compensate for the lack of morphological evidentiality markers via modal verbs, adverbs, and other linguistic strategies. The study underscores the importance of cultural and linguistic context in shaping how speakers signal and interpret the nature of evidence and perception in discourse.
Keywords: evidentiality; perception; Uzbek; English